Impact of tillage and nutrient sources on yield characteristics and production of Ethiopian mustard (Brassica carinata) - SHILPA; SINGH, JANARDAN; MANUJA, SANDEEP; POOJA (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted during winter (rabi) seasons of 2019–20 and 2020–21 at the Research Farm of Chaudhary Sarwan Kumar Himachal Pradesh Krishi Vishvavidyalaya, Palampur, Himachal Pradesh to study the impact of tillage and both organic and inorganic fertilizer sources on the yield characteristics and yield of mustard (Brassica carinata A. Braun). The experiment was conducted in a split-plot design (SPD) consisted of 12 treatments having 3 tillage practices [zero tillage (ZT); reduced tillage (RT); and conventional tillage (CT)] in main plots along with 4 nutrient sources [75% and 100% of the recommended dose of nitrogen (RDN) applied through farmyard manure (FYM) and 75% and 100% of the recommended dose of fertilizer (RDF)] in sub-plots. Reduced tillage resulted in a noticeably higher count of primary (5.32 and 4.75) and secondary branches/plant (13.52 and 11.00), siliquae/ plant (127.1 and 102.3), seeds/siliqua (11.63 and 9.83), seed yield (1134.6 and 955.4 kg/ha), straw yield (3415.2 and 2810.1 kg/ha), biological yield (4549.8 and 3765.5 kg/ha), production efficiency (6.75 and 5.62 kg/ha/day), and monetary efficiency (0.71 and 0.48) of mustard, which was comparable to conventional tillage (CT). Among various nutrient sources, the application of 100% RDF resulted in a significantly greater number of yield attributes and overall yield of mustard, comparable to that of 75% RDF. Correlation analyses indicated that factors such as the number of primary and secondary branches, siliquae/plant, seeds/siliquae, test weight, and final plant stand exhibited a positive and significant relationship with mustard yield. It was concluded that among the different tillage practices, reduced tillage (RT) was found to be most effective for enhancing mustard yield, while with respect to nutrient sources, 100% RDF proved to be superior. The interaction effects of the various treatments were found to be non-significant over both the years of study.